Diagnosis of Papulonecrotic Tuberculid with Chronic Kidney Disease- A Rare Case Report. - Muhammad Adeel; Syed Nayab Haider (University of Lahore, 2022)
A 56-year old male with pulmonary tuberculosis and non-compliant to anti-tuberculosis therapy presented with multiple skin eruptions over the shins and hands for 2 months. Clinical features and skin biopsy were indicative of Papulonecrotic  tuberculid, hence, he was put on renal adjusted ATT due to his worsening serum creatinine.